DETERMINANTS AFFECTING THE TEACHING OF PHYSICAL EDUCATION TO LEARNERS WITH DIFFERENT KINDS OF DISABILITIES-PE TEACHER PREPAREDNESS - Mugweru, Mary; Munayi, Simon; Chumba, Janet; Gathoni, Benson (African Journal of Education and Practice, 2022)
Purpose: The purpose of this study was to investigate determinants affecting the teaching of physical education to learners with different kinds of disabilities such as the physically challenged, visually and hearing impaired in public primary schools having a special unit in Nairobi City County, Kenya. The research highlighted teacher preparedness as a major concern. Methodology: The study utilized the descriptive survey research design. Data was drawn from 7 public primary schools offering a special unit in Nairobi County Kenya, this included 16 PE teachers. Data was collected using questionnaires administered to PE teachers. Findings: The study revealed that the PE teachers have relevant teaching experiences and are qualified as most are trained up to postgraduate level. It was noted that the teachers were trained in special needs education, however, the majority were not trained in adapted physical education. This hindered understanding and the delivery of physical education to the LWDS. It posed a challenge to them as they are not able to modify facilities, equipment, and activities to suit the needs of LWDs. Unique Contribution to Theory, Practice and Policy : The study recommends that physical education teachers need to be regularly provided with adequate in service training especially in adapted physical education. This will ensure that the goals of inclusion are attained hence contributing to the delivery of physical education to LWDs and education growth and development for all.